Stat5-dependent cardioprotection in late remote ischaemia preconditioning. Issue 5 (22nd January 2018) - Chen, Hui; Jing, Xin-Yue; Shen, Yu-Jun; Wang, Tian-Lin; Ou, Chen; Lu, Sheng-Feng; Cai, Yun; Li, Qian; Chen, Xia; Ding, Ya-Juan; Yu, Xiao-Chun; Zhu, Bing-Mei
Abstract: Aims: To study the protective effects of late remote ischaemic preconditioning (RIPC) against myocardial ischaemia/reperfusion (I/R) injury and determine whether Stat5 is involved in this protection by using cardiomyocyte-specific Stat5 knockout mice ( Stat5-cKO ). Methods and results: Mice were exposed to lower limb RIPC or sham ischaemia. After 24 h, the left anterior descending artery (LAD) was ligated for 30 min, then reperfused for 180 min. The myocardial infarct size (IS), apoptotic rate of cardiomyocytes, and serum myocardial enzymes were measured to evaluate for cardioprotective effects. Heart tissues were harvested to determine the cardiomyocytes' anti-apoptotic and survival signaling. When compared with the Stat5 fl/fl mice without RIPC, Stat5 fl/fl mice with RIPC ( Stat5 fl/fl +RIPC + I/R) displayed a decreased myocardial IS/LV (16 ± 1.5 vs. 30.1 ± 3.1%, P < 0.01; IS/ area at risk (AAR), 42.2 ± 3.5 vs. 69.2 ± 4.9%, P < 0.01), a reduced cardiomyocyte apoptotic rate (2.1 ± 0.37 vs. 5.5 ± 0.53%, P < 0.01), and lower creatine kinase (CK), lactate dehydrogenase (LDH), and creatine kinase-MB (CK-MB) levels. To the contrary, the Stat5-cKO mice ( Stat5 fl/fl ; Tnnt2 Cre mice with Doxycycline treatment for 7 days) did not exhibit any effect of RIPC-induced cardioprotection. Activation of STAT5 protein was significantly higher in the Stat5 fl/fl +RIPC + I/R group than in the Stat5 fl/fl +I/R group, while there was no significant difference between the Stat5-cKO + RIPC + I/R and the Stat5-cKO + I/R group. Further analyses with heart tissues detected decreased protein expressions of cytochrome c (Cyt c) and cleaved Caspase-3 in the Stat5 fl/fl +RIPC + I/R mice, along with increased anti-apoptotic molecules, including B-cell lymphoma-extra large (Bcl-xL) and B-cell lymphoma-2 (Bcl-2); such changes were not noted in the Stat5-cKO + RIPC + I/R mice. Additionally, RIPC increased cardiac hypoxia inducible factor-1 (HIF-1α) and interleukin-10 (IL10) protein levels and caused activation of AKT, phosphatidylinositol 3 kinase (PI3K), and vascular endothelial growth factor in the heart of the Stat5 fl/fl mice. However, these changes were completely inhibited by the absence of Stat5. Conclusions: These results suggest that RIPC-induced late cardioprotection against myocardial I/R injury is Stat5-dependent and is correlated with the activation of anti-apoptotic signaling and cardiomyocyte-survival signaling.